(untitled) (London, 1978)
The majority of chapters were specially prepared for, or were discussed as a result of, the first conference of the I.G.U. Working Group on Industrial Geography that was held at the London School of Economics and Political Science, London, England, in September 1974
Keywords: Công nghiệp hóa,Khu kinh tế,Khu công nghiệp,Industrial location,Industrialization,Regional economics